Analysis of Sex Education Learning Methods for Early Childhood: The Role of Parents and Family - Alfiya, Luluk; Azis, Abdul (Journal Ligundi of Community Service, 2026)
Background. Early childhood education plays a critical role in shaping children's values and behaviors. Sex education, a fundamental aspect of life skills education, is increasingly recognized as an important subject for young children. However, how to effectively teach sex education to early learners remains a complex challenge, with particular emphasis on the roles of parents and family in this educational process. Purpose. This study aims to analyze the effectiveness of various learning methods for sex education in early childhood, focusing on the involvement of parents and the family as primary educators. Specifically, the research explores how different approaches to teaching sex education can influence young children's understanding of gender roles, body awareness, and respect for personal boundaries. Method. The study utilized a mixed-methods design, surveying 200 parents and educators in early childhood institutions. Additionally, interviews and focus groups were conducted to gather qualitative insights into the role of family dynamics in the implementation of sex education programs. The data collected were analyzed using both statistical and thematic analysis. Results. The results indicated that children whose families were more actively involved in discussions about sex education demonstrated higher levels of body awareness and respect for privacy. Furthermore, families that used age-appropriate, interactive methods such as storytelling, role-playing, and guided discussions were found to have a positive impact on children's understanding of sex education topics. Conclusion. This study underscores the significant role of parents and family in early childhood sex education. It suggests that effective sex education for young children requires a collaborative approach between educators and families, incorporating both structured and informal learning methods. Future research should focus on developing comprehensive sex education frameworks that support family involvement in various cultural contexts.